2017
DOI: 10.1021/acsphotonics.7b00680
|View full text |Cite
|
Sign up to set email alerts
|

Polaritonic Chemistry with Organic Molecules

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in:El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription AbstractWe present an overview of the general concepts of polaritonic chemistry with organic molecules, i.e., the manipulation of chemical structure that can be achieved through strong coupling between confined light modes and organic molecules. Strong coupling and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
484
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 404 publications
(489 citation statements)
references
References 109 publications
4
484
1
Order By: Relevance
“…The splitting of the atomic peak at 14 800 cm −1 in the middle right panel of figure 1 as well as the appearance of purple colored peaks near 15 100 cm −1 indicates that a considerable mixing of the atomic and molecular states occurred. Increasing the atom number to N a while keeping the cavity field strength fixed leads to (1) an √ N a times increased effective atom-cavity coupling, resulting in a shift in the atomic transition frequency, (2) an N a times increased atomic line strengths, and (3) the appearance of N a − 1 dark states, see lower left panel of figure 1. Our numerical results show, as expected, that these dark states have no significant contribution to the spectrum (see lower right panel of figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The splitting of the atomic peak at 14 800 cm −1 in the middle right panel of figure 1 as well as the appearance of purple colored peaks near 15 100 cm −1 indicates that a considerable mixing of the atomic and molecular states occurred. Increasing the atom number to N a while keeping the cavity field strength fixed leads to (1) an √ N a times increased effective atom-cavity coupling, resulting in a shift in the atomic transition frequency, (2) an N a times increased atomic line strengths, and (3) the appearance of N a − 1 dark states, see lower left panel of figure 1. Our numerical results show, as expected, that these dark states have no significant contribution to the spectrum (see lower right panel of figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the effect on the kinetics has been observed to increase as the collective coupling intensifies, as a consequence of the large number of molecules present in a sample. 1 These observations are reminiscent of the description of light-matter coupling in terms of hybrid states known as polaritons, [7][8][9][10][11][12] which successfully explains the optical properties of these systems. [13][14][15][16][17] Recently, it has been suggested that a class of nonadiabatic charge transfer reactions would experience a catalytic effect from resonant collective coupling between high-frequency modes and infrared cavity modes; the mechanism relies on the formation of vibrational polaritons which feature reduced activation energies compared to the bare molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The high flexibility of the polaritonic properties has been assessed for both realized 20,24,25 and potential applications 13,26 giving birth to a new branch of chemistry 27 : the so-called polaritonic chemistry. 28 When a resonant mode is coupled to electronic transitions, the molecules exhibit enhanced spontaneous emission at both the collective and single molecule level [29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%